Explorative Study of Pharmacokinetics and Pharmacodynamics after Change in Basal Insulin Infusion Rate - Ihlo, Charlotte A. (Diabetes Technology Society, 2011)
BACKGROUND: The use of insulin pumps is rapidly increasing and new, technologically more advanced pumps are continuously being developed. It is of interest to assess the clinical relevance of the many technical features of these pumps, e.g., the effect on pharmacokinetics and pharmacodynamics with change in infusion rate. METHOD: The aim of this study was to explore the sequence of pharmacokinetic and pharmacodynamic changes after dose doubling of the basal insulin infusion rate with subcutaneous bolus insulin injections once an hour, continuous subcutaneous insulin infusion, and continuous intravenous insulin infusion. Ten type 1 diabetes mellitus patients were included. The insulin doses were calculated based on the habitual insulin doses. The study was designed as an open-labeled, single-center, randomized, crossover exploratory trial. RESULTS: Dose doubling of the basal insulin infusion rate with the three different administration protocols did not result in any clinically relevant differences in the time courses of the pharmacokinetic and pharmacodynamic parameters. With all three administration protocols, we observed a time interval of more than 6 hours before a new steady state of insulin was achieved. CONCLUSIONS: Our results indicate that frequent changes in basal subcutaneous insulin infusion rates are not of significant clinical relevance on a 24-hour basis. Regarding technological features of subcutaneous insulin pumps, no discernable advantages of increasing pump stroke frequency were found. This indicates that pump stroke frequency sophistication might not be of clinical relevance in pumps used for basal subcutaneous insulin infusion.